Pengaruh Budaya Kerja dan Kepemimpinan terhadap Disiplin Kerja Pegawai pada Dinas Pendidikan Kota Gorontalo - Pakaya, Syaiful (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2020)
This study aims to determine how much influence work culture and leadership partially and simultaneously on the work discipline of employees at the Gorontalo City Education Office. The sampling method used in this study is the census method, namely the number of samples in the study is less than 100. The main point is through a list of statements that are tested through validity and reliability tests. The analysis method used is the path analysis method. The first test results show that the variables of work culture (X1) and leadership (X2) have a simultaneous effect on employee work discipline. The results of testing the second hypothesis show that work culture (X1) partially has a positive and significant effect on employee work discipline. The third test results indicate that the leadership variable (X2) partially has a positive and significant effect on employee work discipline.